Hematological and Inflammatory Markers in Preterm vs. Term Labor: A Comparative Study in Tertiary Care Hospital - Laul, Abhishek Sanjay (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: Preterm labor as labor that starts before the completion of 37 weeks of pregnancy is a hazard to the health of both mother and the baby. It is associated with high incidence of neonatal deaths and complications because of several factors that precede its occurrence including hematological and inflammatory indices. These kinds of researches are important for elaborating specific approaches which can help to control and perhaps prevent preterm labor. Present study was aimed to determine the levels of hematological and inflammatory markers in women experiencing preterm labor, and women under term Labour, to be compared and understand the different labor conditions. In preterm and term laboring women, it was found that platelet count was lower and hemoglobin was higher with increased WBC count compared with non-laboring women. More precisely, it was established that mean platelet count in preterm Labour was 245 000/µL and mean hemoglobin was 11,2 g/dL which is statistically lower than in term Labour (290 000/µL and 12,5 g/dL respectively). The mean white blood cell count in the preterm infants was 11,800/µL while the mean value in term infants was 9,500/µL. Therefore, it can be concluded that the hematological and the inflammatory markers of women with preterm Labour differ from those with term Labour. Decreased platelet count and hemoglobin as well as increased white blood cells, CRP, and IL-6 levels support the idea about preterm labor as a systemic disease accompanied by inflammatory processes.Keywords: Preterm labor, CRP, IL-6, WBC, ELISA